Buck intercalado para carregamento de baterias - Santos Filho, Roberto Bastos dos (2019)
This work has as main objective the design and implementation of an interleaved buck converter. This topology will serve to be used as a charge controller for batteries by inserting a photovoltaic panel. The reason for using this converter is because it is possible to carry out a project with low voltage and current ripple, reduction of semiconductor stresses, as well as reducing the output current ripple, making it possible to use a non-polarized capacitor increasing system life. These characteristics are possible because in each cell, consisting of a MOSFET, an inductor and a diode, the current is divided, and later superimposed on the emph node that connects the capacitor and the charge. Initially, a review of the photovoltaic panel literature showing the construction nomenclature and relevant information for implementation is presented, followed by battery charging techniques are presented, closing with a review of the main topologies of isolated converters with main focus on the emph buck for being essential for understanding the design criteria of this work. Analyzes and equations are performed demonstrating design methodologies and implementation of the interleaved buck converter, operating steps and the calculations for the components to be used. Later the simulation results are presented and discussed, as well as the experimental results in sequence. The closing is done with the presentation of the conclusion and the works to be developed in the future.